1997
DOI: 10.1074/jbc.272.45.28779
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-resistant Human Melanoma Cells Are Deficient in ISGF3 Components, STAT1, STAT2, and p48-ISGF3γ

Abstract: The mechanism of IFN resistance was examined in three long-term cell lines, SK-MEL-28, SK-MEL-3, and MM96, exhibiting significant variation in responsiveness to the antiproliferative and antiviral effects of type I IFNs. The JAK-STAT components involved in IFN signal transduction were analyzed in detail. After exposure to IFN, activation of the IFN type I receptor-linked tyrosine kinases, JAK-1 and TYK-2, was detected at similar levels in both IFN-sensitive and IFN-resistant cell types, indicating that IFN res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 41 publications
(28 reference statements)
8
179
1
Order By: Relevance
“…STAT genes included in the array (2, 4, 5a and 5b) were found to be expressed at relatively low levels (nAD ≤ 50) in all cell lines, irrespective of IFN-α responsiveness. These results are in agreement with data obtained by using different technologies, suggesting the presence of relatively functional signal transduction in IFN-α insensitive cells (Ralph et al, 1995;Wong et al, 1997). Interestingly, similar results were also obtained by testing some of the cell lines under investigation in the current work by conventional gene and protein expression techniques (Pansky et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…STAT genes included in the array (2, 4, 5a and 5b) were found to be expressed at relatively low levels (nAD ≤ 50) in all cell lines, irrespective of IFN-α responsiveness. These results are in agreement with data obtained by using different technologies, suggesting the presence of relatively functional signal transduction in IFN-α insensitive cells (Ralph et al, 1995;Wong et al, 1997). Interestingly, similar results were also obtained by testing some of the cell lines under investigation in the current work by conventional gene and protein expression techniques (Pansky et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, activated STAT1 was also shown to negatively regulate angiogenesis, tumorigenicity and metastasis of tumour cells (Huang et al, 2002). STAT1 deficiency has also been found in a variety of tumour cell lines and this deficiency is responsible for the lack of INF-g-mediated tumour suppression effects (Wong et al, 1997;Abril et al, 1998;Sun et al, 1998;Pansky et al, 2000). Therefore, it was not unexpected that constitutively activated STAT1 was found in only eight (13.1%) of the 61 NPC specimens.…”
Section: Discussionmentioning
confidence: 98%
“…Loss of components of the signaling machinery may be regarded as an alternative strategy to attain a growth advantage: recently, melanoma cells resistant to the anti-proliferative e ect of IFNa were described to contain less STAT1 than IFNa-sensitive cells. Overexpression of STAT1 improved the responsiveness to IFNa (Wong et al, 1997). It will be of interest to ®nd out whether defects in Jak/ STAT signaling contribute to IL-6-resistance observed in several late-stage melanoma cell lines (Lu et al, 1992(Lu et al, , 1993.…”
Section: Growth Inhibition Of Melanoma Cells By Il-6-type Cytokines Dmentioning
confidence: 99%